Macrophyte species uniqueness is driven by habitat integrity, sediment structure, and spatial components in streams around the Amazon National Park - Cabral, Guilherme Sampaio; Silva, Ronaldo Souza; Bomfim, Francieli F.; Juen, Leandro; Casatti, Lilian [UNESP]; Montag, Luciano; Dias-Silva, Karina; Oliveira-Junior, José Max Barbosa; Michelan, Thaisa Sala (Elsevier, 2025)
Natural landscapes have been altered due to the increasing demand for natural resources, leading to changes in physicochemical characteristics and species composition of several systems, including the aquatic. This study identified the streams and species that contributed the most to macrophyte beta diversity within and surrounding the Amazon National Park. We also investigated the factors (local, spatial, and land-use) influencing the community structure. Biological and environmental data were obtained by field sampling in 29 streams (17 within the park and 12 outside). Land-use data were obtained by remote sensing (satellite imagery). The highest species contribution to beta diversity was observed in species with a high frequency of occurrence. The greater local contribution to beta diversity (LCBD) and the highest species richness were observed outside the park. Habitat integrity, fine substrate, and spatial components (i.e., geographic distance) negatively influenced LCBD, highlighting the effect of environmental filtering and dispersion processes on stream macrophytes. Land use variables did not significantly affect macrophytes LCBD. Our findings provide an important snapshot of how different factors (local, spatial, and land use changes) interact in determining macrophyte beta diversity in streams within and around the Amazon National Park. The study also underscores the importance of conservation units to preserve stream ecosystems' natural characteristics and habitat integrity.
Keywords: Aquatic plants; Beta diversity; Conservation; Land use changes; Local contribution; Species contribution